Association between preterm birth and the renin−angiotensin system in adolescence: influence of sex and obesity. Issue 10 (October 2018) - South, Andrew M.; Nixon, Patricia A.; Chappell, Mark C.; Diz, Debra I.; Russell, Gregory B.; Jensen, Elizabeth T.; Shaltout, Hossam A.; O'Shea, T. Michael; Washburn, Lisa K.
Abstract : Objectives: Preterm birth appears to contribute to early development of cardiovascular disease, but the mechanisms are unknown. Prematurity may result in programming events that alter the renin−angiotensin system. We hypothesized that prematurity is associated with lower angiotensin-(1-7) in adolescence and that sex and obesity modify this relationship. Methods: We quantified angiotensin II and angiotensin-(1-7) in the plasma and urine of 175 adolescents born preterm and 51 term-born controls. We used generalized linear models to estimate the association between prematurity and the peptides, controlling for confounding factors and stratifying by sex and overweight/obesity. Results: Prematurity was associated with lower plasma angiotensin II ( β : −5.2 pmol/l, 95% CI: −10.3 to −0.04) and angiotensin-(1-7) (–5.2 pmol/l, 95% CI: −8.4 to −2.0) but overall higher angiotensin II:angiotensin-(1-7) (3.0, 95% CI: 0.9−5.0). The preterm−term difference in plasma angiotensin-(1-7) was greater in women (−6.9 pmol/l, 95% CI: −10.7 to −3.1) and individuals with overweight/obesity (−8.0 pmol/l, 95% CI: −12.2 to −3.8). The preterm−term difference in angiotensin II:angiotensin-(1-7) was greater among those with overweight/obesity (4.4, 95% CI: 0.6−8.1). On multivariate analysis, prematurity was associated with lower urinary angiotensin II:angiotensin-(1-7) (−0.13, 95% CI: −0.26 to −0.003), especially among the overweight/obesity group (−0.38, 95% CI: −0.72 to −0.04). Conclusion: Circulating angiotensin-(1-7) was diminished whereas urinary angiotensin-(1-7) was increased relative to angiotensin II in adolescents born preterm, suggesting prematurity may increase the risk of cardiovascular disease by altering the renin−angiotensin system. Perinatal renin−angiotensin system programming was more pronounced in women and individuals with overweight/obesity, thus potentially augmenting their risk of developing early cardiovascular disease.